Peace processes in Northern Ireland and Turkey : rethinking conflict resolution - Kadıoğlu, İ. Aytaç (Edinburgh studies on modern Turkey., 2020)
This text challenges the notion of 'conflict resolution' in the Northern Irish and Turkish-Kurdish peace processes, both far-reaching ethno-nationalist conflicts in the post-Cold War era.